Analysis of Current Status of Clinical Trial Registrations in Andrological Diseases: Insights from ClinicalTrials.gov and ICTRP Databases - Li-Xing Lei; Ke-Cheng Li; Wen-Hao Yu; Jun-Long Feng; Hua-Nan Zhang; Mao-Ke Chen; Wen-Xuan Dong; Ji-Xuan Chen; Jie Li; Ji-Sheng Wang; Liang Han; Bin Wang (American Journal of Men's Health)
This study aims to analyze the registration information and outcome transparency for five common andrological diseases, as well as the factors influencing result availability. A comprehensive search was performed on ClinicalTrials.gov and the International Clinical Trials Registry Platform (ICTRP) to retrieve all clinical trial registration data related to the five defined andrological diseases from the inception of these databases up to September 1, 2024. The search extracted key trial details, including status, type, intervention, and result availability. Of 8,132 trials retrieved, 642 were analyzed. Among these, 259 trials (40.34%) reported results via ClinicalTrials.gov, ICTRP, or publications, while 113 trials (17.60%) made results publicly available on ClinicalTrials.gov or ICTRP. Among the five andrological diseases, male infertility had the highest rate of result availability (37/74, 50%), whereas benign prostatic hyperplasia exhibited the lowest (71/190, 37.37%). No significant differences were found across diseases (χ 2  = 3.722, df  = 4, p  = .435). Factors such as study status, blinding, interventions, center type, location, and duration significantly influenced result availability, whereas study type, stage, funding, outcome indicators, and sample size did not. Clinical trials on andrological conditions show major gaps in registration and result disclosure, with low reporting rates and prevalent non-reporting and selective reporting. Developed countries dominate trial registration and result disclosure while developing countries have limited participation. Trial characteristics also influence result disclosure rates. These challenges compromise the integrity and credibility of research data, impede clinical practice, and hinder the progress of medical research. Measures are needed to improve transparency, reduce selective reporting, and enhance the rigor and credibility of andrology research.